2018
DOI: 10.3390/en11061414
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Influence Factors of Acoustic Emission Activity in Coal Failure Process

Abstract: Stress-dominated coal and gas outburst disaster has become one of the main safety problems in deep coal mines. Acoustic emission (AE) or microseismic technology has been viewed as a promising method that can effectively reflect the stress and stability status of rock mass. The AE activity precursor of coal failure is the theoretical basis of this technology. In this study, AE experiments in failure process of coal specimens with different properties and under different stress conditions were performed in labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…He et al [19] carried out single-face dynamic unloading tests under truetriaxial conditions for limestone samples, pointing out that the frequency amplitude of AE signals varies with coal bump stages. Yang et al [20] reported that the external stress condition has a transition effect on the AE event energy distribution and AE activity pattern. Kuksenko et al [21] found that the relaxation of the polarization is identical in nature for both cases and is basically a thermally activated process.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [19] carried out single-face dynamic unloading tests under truetriaxial conditions for limestone samples, pointing out that the frequency amplitude of AE signals varies with coal bump stages. Yang et al [20] reported that the external stress condition has a transition effect on the AE event energy distribution and AE activity pattern. Kuksenko et al [21] found that the relaxation of the polarization is identical in nature for both cases and is basically a thermally activated process.…”
Section: Introductionmentioning
confidence: 99%
“…Near peak strength point, with the increase of initial stress, the change trend of amplitude changed from "low-high" to "low-highlow" and the signal quantity is less and more concentrated, which indicates that the energy distribution characteristic changed from dispersed under low initial stress to concentrated under high initial stress; however, the energy remained calm all the time, which indicates that the failure form of saturated limestone was gradual. On the other hand, near rock-failure point, with the increase of initial stress, the change trend of amplitude changed from "intermittent gradual decrease" to " not appear," which indicates that the rock-failure behavior and AE event evolution form changed from ductility to brittleness [25]. The phenomena above can be used as the precursory information of peak strength point and rockfailure point.…”
Section: Different Initial Stressesmentioning
confidence: 94%
“…In the production process of an underground coal mine, production activities such as roadway excavation and coal face mining will cause strata movement and stress redistribution around the stope. us, a mining stress field is generated, and the stress changes continuously with mining activity [1][2][3][4]. Its superposition with the original rock stress acts on surrounding coal seams, the roof, and floor strata, which is a typical cyclic loading condition [5][6][7].…”
Section: Introductionmentioning
confidence: 99%